Scale to Measure Farmers’ Attitude towards ICT-Based Agro-Advisory Services - Paliwal, Harshit; Arun Kumar Singh; Sarvesh Kumar Singh; Prashish Singh (Indian Journal of Extension Education, 2025)
In recent years, rapid advancements in Information and Communication Technologies (ICT) have transformed agricultural extension by enabling timely, accurate, and farmer-specific agro-advisories. Farmers’ attitudes play a crucial role in determining the acceptance, sustained use, and practical application of such services. Therefore, a study was undertaken in 2025 to develop and standardise an attitude scale for farmers toward ICT-based agro-advisory services. An initial pool of 110 statements was generated through literature review, farmer interactions, and expert consultations. After item screening and statistical analysis, 48 statements were finalised under six dimensions: Perceived Usefulness, Trust and Credibility, Accessibility and Convenience, Responsiveness and Personalisation, Adoption Behaviour, and General Attitude. Content validity was assessed through expert evaluation, wherein Item-level CVI values ranged from 0.80 to 0.95, and the Scale-level CVI/Average (S-CVI/Ave) was 0.91, reflecting excellent relevance. A multistage sampling procedure followed by Probability Proportional to Size (PPS) sampling was used to ensure proportional representation of farmers across selected villages. Reliability testing confirmed strong internal consistency, with Cronbach’s alpha 0.86 and Split-Half reliability (Spearman-Brown coefficient) 0.89. The validated scale can serve as a useful tool for researchers and extension stakeholders to assess farmer readiness and design more user-centric ICT advisory systems.